Determination of correlation between plant distribution and ecological factors in Narowal district Punjab, Pakistan - Zereen, Arifa; Ahmad, Sheik Saeed; Khan, Zaheer-Ud-Din; Jahan, Alman (Bangladesh Journal of Botany, 2018)
In order to study correlation between ecological factors and vegetation distribution, multivariate analysis was undertaken. Thirty four plant families represented by 59 species were recorded. For classifying the plant communities TWINSPAN (Two Way Indicator Species Analysis) software program was used. After analysis plants were categorized into two large (major) and six small (sub) communities. Water and soil samples were analyzed for pH, EC, soil colour and soil water content. Canonical correspondence analysis (CCA) was employed to correlate species distribution pattern to environmental factors. Results showed that despite many variables being strongly correlated, they were of little value in grouping together of species. However, soil pH and electrical conductivity (EC) had effects on distribution of vegetation.